2013
DOI: 10.1504/ijmie.2013.050812
|View full text |Cite
|
Sign up to set email alerts
|

The impact of student retention strategies: an empirical study

Abstract: Crisp, J. (2013) 'The impact of student retention strategies: an empirical study', Int. J. Management in Education, Vol. 7, Nos. 1/2, pp.22-43. AuthorsElke Abstract: A major concern for institutions and instructors is the high dropout rate of students in online courses. This study investigated the impact of student retention strategies on retention rates in an online information systems course. A treatment group exposed to retention strategies related to student engagement, learning communities, student serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 29 publications
2
43
0
1
Order By: Relevance
“…Some studies find no significant relationship between faculty participation and course completion rates (Cochran et al 2014;Grandzol and Grandzol 2010;Leeds et al 2013). In fact, some even conclude that "efforts to include extensive faculty feedback and interaction in online courses (Bocchi, Eastman, and Swift 2004) may actually be counterproductive" (Grandzol and Grandzol 2010, 10).…”
Section: Success and The Online Studentmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies find no significant relationship between faculty participation and course completion rates (Cochran et al 2014;Grandzol and Grandzol 2010;Leeds et al 2013). In fact, some even conclude that "efforts to include extensive faculty feedback and interaction in online courses (Bocchi, Eastman, and Swift 2004) may actually be counterproductive" (Grandzol and Grandzol 2010, 10).…”
Section: Success and The Online Studentmentioning
confidence: 99%
“…In a 2013 study, Leeds et al implemented all the best practices outlined by Angelino, Williams, and Natvig (2007). Although the study included a number of resource-intensive interventions, Leeds et al (2013) found no significant improvement in retention. Similarly, Tirrell (2009) examined online community college instructors and found that those who used Chickering and Gamson's (1987) seven principles for good practice in undergraduate education, including instructor-student contact, did not have lower attrition rates.…”
Section: Success and The Online Studentmentioning
confidence: 99%
“…A ocorrência da situação em que estudantes iniciam mas não terminam seus cursos gera desperdícios sociais, acadêmicos e econômicos (Tinto, 1975;Lobo, Montejinas, Hipólipo y Lobo, 2007;Park y Choi, 2009;Nistor, 2010;Leeds, 2013).…”
unclassified
“…A team of researchers at Kennesaw State University (Leeds et al 2013) conducted an extensive experiment in a business information systems course that tested the proposals suggested by Angelino, Williams, and Natvig (2007). Students selfregistered for online sections that were then randomly assigned to different strategies for addressing attrition and performance.…”
Section: Resultsmentioning
confidence: 99%
“…This intuitive claim has not been validated in the most rigorous of empirical tests. This suggests the need for future research that integrates the existing scholarship on student characteristics (Wojciechowski and Palmer 2005), personality and learning styles (Harrington andLoffredo 2010 andCartnal 1999), and innovative strategies (Angelino, Williams, andNatvig 2007, andLeeds et al 2013). The stakes are high in this endeavor because, without an answer, the profession is writing off 30% of the students in the online classes.…”
Section: Resultsmentioning
confidence: 99%